SEJARAH TAFSIR MTA (MAJLIS TAFSIR AL-QUR'AN) - Asif, Muhammad (AL ITQAN: Jurnal Studi Al-Qur'an, 2015)
Majelis Tafsir Al-Qur’an (MTA) recently claims that they don’t make exegesis of  Al-Qur’an. But this opinion seems like different from the reality. It is fact that MTA has an exegesis  book and continues to  make exegesis of Al-Qur’an. This article describes the history of development and  MTA exegesis dynamics. Since the exegesis  was taught by the founder of MTA, Abdullah Thufail, MTA’s exegesis isn’t static. But has got many corrections, change, until revision. It is predicted that  MTA’s exegesis is going to get development and  continual.   Key word: MTA, tafsir, revisi, berkelanjutan.